Multi-criteria decision aid to solve a leave of absence problem - Rocha, Miriam; Silva, Rafael; Dantas, Aline; Dantas, Saulo; Freitas, Liane; Salomon, Valério [UNESP] (My University, 2014)
This paper aims to present a practical application of the model of multi-criteria decision known as Analytic Hierarchy Process (AHP) in order to solve a leave of absence problem of professors from a Federal Institution of Higher Education (IFES) in Brazil. Despite the teaching career of the IFES indicate that the professors seeks a PhD degree, there are still a significant number of them without it on the IFES located in countryside mainly. These institutions, in particular, needs to plan the training of their professors, ordering the outputs of teachers, without prejudice to the academic activities of IFES. Based on a real case, an institution in the interior of the northeastern region of the country, a survey was made for the measurement and evaluation of criteria through a brainstorming at IFES. The following criteria were established: number of publication, age, time of establishment, the proportion of teachers with a doctorate in the course and accepted at some doctoral course. Then, data were collected from teachers and doctors who wished not a doctorate. From this we applied the AHP method, which allowed the ordination of clearances of these teachers. This result was presented to the academic management of IFES found to be feasible, proving to be an effective method for this multi-criteria problem.
Keywords: AHP; Decision; Educational institution